Graduação histológica e expressão de metaloproteinases (MMP-9 e MMP-2) e seus inibidores (TIMP-1 e TIMP-2) na glândula mamária canina neoplásica - FERREIRA, Hugo Henrique (2012)
In bitchs, mammary glands are the most common sites for the occurrence of neoplasms. To evaluate the biological behavior of these lesions is routinely employ descriptive histological methods that, combined with histological grading, help predict prognosis of these diseases. The imbalance between the amount of tissue matrix metalloproteinases (MMPs), proteolytic enzymes involved in physiological and pathological processes, and their inhibitors (TIMP), plays an important role in development and tumor invasion. To evaluate the biological behavior of some common types of breast tumor bitches this research was divided in two steps. The first one was correlating histological classification and degree of mammary neoplasms in bitches, and to correlating the degree of malignancy and tumor size. For this, 119 samples were evaluated in canine mammary tumors, all tumors were considered disorders of the growth of canine mammary gland, including neoplastic (benign and malignant) and non-neoplastic (hyperplastic changes). All tumors were classified and only the malignant were graded histologically and correlated with tumor size. It was concluded that the complex carcinoma is the most common cancer histological type and which has the lowest histological grade compared to other malignant tumor types. Further, neoplasms larger than five centimeters were predominantly malignant (92,3% or 12/13) and no correlation was observed between tumor size and histologic grade. The relation between histological classification and graduation helped in microscopic description of malignant mammary tumors in bitches. The second step was to evaluate the expression of MMP-9, MMP-2 TIMP-1 and TIMP-2 in normal and neoplastic canine mammary tissue. For this purpose it was selected 48 samples of canine mammary tissue, 14 complex carcinomas (CC), 13 tubulopapillary carcinoma (TC), six simple mammary adenoma (MA) and 15 normal breast (MN), and submitted to technical immunohistochemistry for the evaluation of the intensity staining and the number of epithelial and stromal cells selected. Differences were observed in the expression of MMP-9 and TIMP-1 and TIMP-2 according to the mammary histomorphology. The MMP-9 showed higher expression in epithelial and stromal cells of the CC and CT compared to MN. It was found a lower expression of TIMP-1 in stromal cells of the CC and overexpression of TIMP-2 in epithelial cells of the CT. Also a positive correlation between MMP-9 and TIMP-1 and the intensity staining and number of epithelial and stromal cells marked in MN and between MMP-9 and TIMP-2 on TC neoplastic epithelial cells. It was concluded that there is variation between expression of MMP-9, TIMP-1 and TIMP-2 among the tumor types, and a positive correlation between TIMP-1 and MMP-9 in normal mammary gland and between MMP-9 and TIMP-2 in tubulopapilar carcinoma. The balanced expression of MMP-9, MMP-2, TIMP-1 and TIMP-2 is essential for the homeostasis of canine normal mammary gland, while the overexpression of MMP-9 and TIMP-2, and the reduced expression of TIMP-1 in carcinomas represents an appropriate condition to the tumor development.